Recent insights into innate immune nucleic acid sensing during viral infection. (October 2022) - Guy, Coralie; Bowie, Andrew G
Abstract : Recent advances in our understanding of nucleic acid pattern-recognition receptor (PRR) sensing of viruses have revealed a previously unappreciated level of complexity of the host antiviral response. As well as direct recognition of viral nucleic acid by PRRs, viruses also induce the release of host nucleic acid from the nucleus and mitochondria into the cytosol, which boosts nucleic acid activation of antiviral PRRs. Crosstalk and cooperation between DNA- and RNA-recognition signaling pathways has also been revealed, as has direct restriction of viral genomes in an interferon-independent manner by PRRs, and new roles for inflammasomes in sensing viral nucleic acid. Further, newly identified viral-evasion strategies targeting PRR pathways emphasize the importance of nucleic acid detection during viral infection at the host–pathogen innate immune interface. Highlights: DNA sensor interferon-inducible protein 16 also senses viral RNA. RNA viral infection releases mitochondrial DNA that is sensed by DNA receptors. Retinoic acid-inducible gene I both senses and restricts RNA viruses.. NLRP1 senses double-stranded RNA, leading to inflammasome activation. Severe acute respiratory syndrome coronavirus-2antagonizes nucleic acid sensing .